DEVELOPING LEARNING PRACTICE MODEL FOR TOURISM VOCATIONAL HIGH SCHOOL STUDENTS - Kristiyanto, Bambang Noor Achsan (Journal of Vocational Education Studies, 2018)
This study has been done to get a purpose in finding the integrated teaching practice in the hotel accommodation and the traveling tourism program in the vocational high school. The teaching practice developed includes: (1) communication through telephone; (2) the hotel industry and tourism; (3) reservation and transfer (check-in/out); (4) processing room reservations and travel tickets; (5) processing the transactions and financial statements; and (6) perform clerical and administrative office procedures. This study uses research and development, the stages of research and data collection were conducted at SMK Negeri 4 and SMK Negeri 6 Yogyakara. The development of stage was tried out in Edotel Kenai Yogyakarta. The research and development of integrated model of practicing learning in the skills competency of the hotel accommodation and the traveling tourism program in vocational tourism school produce graduates who are competent in their field and are able to be a highly skilled workforce, independent and ready to use. The students are able to demonstrate the quality and performance in terms of personal attitude: (1) think logically, fast and precise in determining any motion and actions to be undertaken; (2) behave wisely by not leaving ethics and manners at every decision taken; (3) act to determine the steps to be done that can be accounted for. The result of this research to find out the integrated learning practice process proved to be very suitable and effective in improving students' competence in obtaining buzzing standard work practices in the world of business and industry. The applying this model is expected tourism vocational graduates can fill the share of employment in the industrial world and fill labor needs in the community.